Gender, Ethnicity and Teaching Competencies: Do They Influence Intercultural Communicative Competence in Teacher Education? - Marjorie Tovar-Correal; Liliana Pedraja-Rejas (Education Sciences)
Globalization has transformed classrooms into culturally diverse environments, highlighting the critical need to prepare future teachers with skills to address these complexities. This study explores Intercultural Communicative Competence (ICC) as a fundamental skill in initial teacher training (ITT), aligning with Sustainable Development Goal (SDG) No. 4, which promotes inclusive, equitable and quality education. Through a narrative literature review, this research analyzes the main definitions and theoretical models of ICC, examining their relationship to gender, ethnicity and the teaching competencies of the faculty member. The findings highlight the lack of a unified consensus in the conceptualization of ICC, reflecting its dynamic and interdisciplinary nature. The results indicate that while gender does not significantly influence the development of ICC, ethnicity and migrant background are linked to a greater willingness to acquire it. In addition, the reflective and specialized training of the faculty member emerges as a decisive factor in the promotion of the ICC. These findings underscore the need to integrate ICC into initial teacher education plans to better prepare future teachers in multicultural contexts. By addressing equity and cultural diversity, the ICC supports educators in promoting respectful, effective and inclusive interactions, ultimately contributing to the achievement of SDG No. 4. This study enriches the discourse on teacher education and intercultural education by offering practical perspectives for connecting theory with practice in diverse educational contexts.